Honorable ciutadà : in memoriam Joan Reventós / Presentació Narcis Serra i Serra ; Josep M. Ainaud de Lasarte ... [et al.] - Serra, NarcísAinaud de Lasarte, Josep M. ((R) ; 10)
Con textos de Narcís Serra, María Badía, Oriol Civil, Jordi Font, Felipe González, Pasqual Maragall, Remei Margarit, Jordi Marsal, Isidre Molas, Josep Montilla, Raimon Obiols, Lluis María de Puig, Josep Puig, Antoni Siurana, Josep Maria Triginer y Montserrat Tura.